PERANCANGAN SISTEM APLIKASI MANAJEMEN ARISAN ONLINE IDEAMM PT. TIRA SMART FAMILY BERBASIS WEB - Eva Apriliyanti; Heri Haerudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The development of information technology at this time is increasing providing opportunities for everyone companies to have business competitiveness so that companies are required to have an application system that is able to support management in the company's data processing process. The process of processing arisan member data is still done manually where the arisan admin must record the names of the arisan members with a considerable quantity level into the arisan logbook, as well as in payment of arisan money. In addition, the arisan drawing process still uses written paper media. Therefore, a computerized data processing system is needed and can make it easier for users to carry out online social gathering activities. Online gathering is an activity to collect money or goods of value by a number of people who are connected to each other using a network to determine the lottery periodically until all members get it.